2007
DOI: 10.1897/07-052.1
|View full text |Cite
|
Sign up to set email alerts
|

Release of elements to natural water from sediments of Lake Roosevelt, Washington, USA

Abstract: Reservoir sediments from Lake Roosevelt (WA, USA) that were contaminated with smelter waste discharged into the Columbia River (BC, Canada) were examined using three measures of elemental release reflecting varying degrees of physical mixing and time scales. Aqueous concentrations of Cd, Cu, Pb, and Zn in the interstitial water of reservoir sediments, in the gently stirred overlying waters of incubated sediment cores, and in supernatants of aggressively tumbled slurries of reservoir sediments generally were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Paulson and others (2006) measured not only (1) the concentrations of dissolved metals in interstitial water of sediments that were released from solid sediment, but also measured (2) the release rates of bioavailable dissolved metals that were released to the water column during gently stirred incubation core experiments, and (3) the release rates from slurries mixed end-over-end. For all three measures, the highest dissolved copper concentrations were associated with sediment samples collected from the riverine reach near the Canadian border that contained 70 percent slag based on the sediment zinc concentration (Paulson and Cox, 2007).…”
Section: Ccr-692mentioning
confidence: 99%
“…Paulson and others (2006) measured not only (1) the concentrations of dissolved metals in interstitial water of sediments that were released from solid sediment, but also measured (2) the release rates of bioavailable dissolved metals that were released to the water column during gently stirred incubation core experiments, and (3) the release rates from slurries mixed end-over-end. For all three measures, the highest dissolved copper concentrations were associated with sediment samples collected from the riverine reach near the Canadian border that contained 70 percent slag based on the sediment zinc concentration (Paulson and Cox, 2007).…”
Section: Ccr-692mentioning
confidence: 99%
“…the release of elements from contaminated sediments in the Columbia River into pore water, overlying water, and supernatants of aggressively tumbled slurries, and found that under certain conditions, there might be exposure to concentrations of metals sufficient to cause adverse effects [24]. Therefore, the current study employed an experimental design with controlled, fluvial, laboratory exposure settings, and water characteristics comparable to conditions found within the UCR stretch of concern, in order to assess UCR sediment toxicity to early life stages of white sturgeon.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated releases of elements from contaminated sediments in the Columbia River by use of several methods, such as quantification of metals in pore water (interstitial water), overlying water, and supernatants of aggressively tumbled slurries [17,18]. From these studies Paulson and Cox [18] concluded that under certain conditions releases of elements from sediment could result in concentrations of metals in various matrices that might be toxic to aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…From these studies Paulson and Cox [18] concluded that under certain conditions releases of elements from sediment could result in concentrations of metals in various matrices that might be toxic to aquatic organisms. However, the Paulson and Cox [18] study employed techniques to simulate the potential release of metals from sediments under laboratory conditions that are unlikely to be directly applicable to conditions found in the above-mentioned region of concern of the UCR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation